Empowering in Creating Shared Value: Fire-Free Village Program - Iwan Koswara, Indra Ardiyanto, Antar Venus, Agus Rusmana, (Opción, 2019)
The focus of this research is to review the Fire Free Village Program (FFVP) as a solution to the problem of forest fires in Riau Province, Indonesia. This study employed an online survey methodology and semi-structured interview. As a result, as many as 64% of respondents consider that most of their current community members clearly understood; the risks and dangers of fire and haze to environmental and community health. The research concludes that education and socialization efforts were highly successful in the communities that engaged.